Formalization of Banking Supervision c y Eiji Hotori, Mikael Wendschlag, Thibaud Giddey. - Hotori, Eiji.; Wendschlag, Mikael; Giddey, Thibaud; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Palgrave Macmillan, 2022)
This open access book is the first attempt to elaborate the formalization phase of banking supervision in eight developed countries USA, Japan, Sweden, Germany, Switzerland, Belgium, France, and UK. This innovative study in the field of banking supervision history identifies why national histories of banking supervision share similarities, but also remain different and are heavily path dependent. This book will be of great interest not only to financial/economic historians but also to general readers interested in banking supervision, i.e., students, bankers, supervisors, and international officials. Eiji Hotori is Professor of Japanese Economic History at the Yokohama National University. He is also Councilor of the Socio-Economic History Society in Tokyo. He received his Ph.D. in economics from the University of Tokyo. His research interests are in the domestic and comparative history of commercial banking, financial elites, and banking supervision. Mikael Wendschlag is Researcher and Lecturer at the Department for Economic History at Uppsala University, Sweden. He received his Ph.D. in economics from Linköping University. His research concerns financial supervision, financial elites and white-collar crime in history. Thibaud Giddey is Postdoctoral Research Associate of the Global Correspondent Banking ERC-project at the University of Oxford. He previously held visiting positions at Uppsala University, Katholieke Universiteit Leuven and City University London. He obtained his Ph.D. in arts (history) at the University of Lausanne in 2017. His research interests include the history of banking supervision, financial scandals, the development of political and financial elites, comparative public policies, and the history of white-collar crime.
Chapter 1. Motivation and Framework -- Chapter 2. The United States: The First Formalization of Banking Supervision -- Chapter 3. Japan: Formalization of Banking Supervision Including a Reversal -- Chapter 4. Sweden: Early Adopter of Formal Banking Supervision with Incremental Steps -- Chapter 5. Germany: Financial Crises and Formalization of Banking Supervision -- Chapter 6. Switzerland: Formalizing Banking Supervision in the Aftermath of a Crisis, Better Late than Never -- Chapter 7. Belgium: Formalization and Incremental Development of a Supervisor with Increasing Powers and Authority -- Chapter 8. France: Credit Control and Formalization of Banking Supervision.-Chapter 9. The United Kingdom: Financial Globalization and Formalization of Banking Supervision -- Chapter 10. Drivers of the Formalization of Banking Supervision.
Keywords: Finance; International economic relations; Economic history; History; History, Modern; Financial Economics; International Economics; Economic History; Financial History; Modern History